Indiscipline in rehabilitation curriculum regulation- restricting development perspective: A narrative review - Zia, Wajeeha; Mumtaz, Nazia; Ghulam Saqulain; Shahid, Wajiha (Journal of the Pakistan Medical Association, 2022)
Curriculum regulation and its oversight are indispensable and vital components of professional development. Regulatory bodies along with professional organisations have an essential role in curriculum regulation. The Pakistan Speech and Language Pathology Association, a body duly registered under the laws of Pakistan and whose governing body exclusively comprises pathologists with master’s in Speech Language, has taken up the matter of standardisation and uniformity of curriculum with universities and with the Higher Education Commission. The commission regulates the undergraduate curricula, but there remains lack of uniformity in curriculum and its monitoring in Pakistan. The current narrative review was planned to highlight the indiscipline in rehabilitation curriculum development and implementation and its causes. Key Words: Curriculum, Inhibitors, Physical therapy, Regulatory body, Speech language pathology.